Essentials of managing stress - Seaward, Brian Luke (Jones & Bartlett Learning, 2014)
The quintessential stress management text for undergraduate students, Essentials of Managing Stress balances key concepts and academic theory with real-life applications and exercises, allowing students to integrate theory and practice in their own lives. The only textbook of its kind to comprehensively address the relationship between mind, body, and spirit, this fully revised and updated Third Edition includes all-new sections on the sociology of stress and communication skills, with special emphasis on high-tech communications, screen addictions, and social networking. Essentials of Managing Stress also covers environmental disconnect, compassion fatigue, and mindfulness.